Dictionary of international business law - Otto, Lucas (London : Global Professional Pub., 2008)
"The Dictionary of International Business Law is designed to help operating managers deal with the basics of business and legal communication across borders. It is designed to be a convenient and concise multicultural law handbook, offering business people a clear and simple reference for the common words and acronyms used in the United States, the United Kingdom and the European Union. This is particularly important in the three areas of labor law, international finance and import/export. In every case definitions and examples are simple; they are meant to illustrate how a particular concept is used in actual practice." "Managers will find that the concise nature of the dictionary and cross referencing of the always difficult legal and business acronyms will be vital in their everyday pursuit of business."--Jacket.
Keywords: Commercial law -- Dictionaries; Legal terminology